2021
DOI: 10.1111/joor.13170
|View full text |Cite
|
Sign up to set email alerts
|

Signal acquisition and analysis of ambulatory electromyographic recordings for the assessment of sleep bruxism: A scoping review

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 134 publications
(2,671 reference statements)
0
48
0
Order By: Relevance
“…In many of these cases, the symptoms are temporary, the patients themselves are unaware of the symptoms, and active treatment is not required [117,118]. In earlier studies, the estimated prevalence of sleep bruxism awareness was based on reports by parents or sleep partners [121]. Recently, polysomnography with audio-video recording or ambulatory EMG devices have been used for a definite diagnosis [121].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In many of these cases, the symptoms are temporary, the patients themselves are unaware of the symptoms, and active treatment is not required [117,118]. In earlier studies, the estimated prevalence of sleep bruxism awareness was based on reports by parents or sleep partners [121]. Recently, polysomnography with audio-video recording or ambulatory EMG devices have been used for a definite diagnosis [121].…”
Section: Epidemiologymentioning
confidence: 99%
“…In earlier studies, the estimated prevalence of sleep bruxism awareness was based on reports by parents or sleep partners [121]. Recently, polysomnography with audio-video recording or ambulatory EMG devices have been used for a definite diagnosis [121]. Thymi et al [121] suggested that, in future studies using ambulatory EMG instruments, the focus may require to shift to the concept of scoring the whole spectrum of masticatory muscle activity.…”
Section: Epidemiologymentioning
confidence: 99%
“…The use, misuse and validity of SB metrics have been recurrent issues for >30 years, and two “work in progress” consensus papers, and several commentaries on SB definition, classification, and methods of data collection have been published (Casett et al., 2017; Lobbezoo et al., 2018; Lobbezoo, Ahlberg, Raphael, et al., 2018; Manfredini et al., 2019, 2020; Meira & Ettlin, 2018; Raphael et al., 2016b; Stuginski‐Barbosa et al., 2017; Thymi et al., 2021) The latest international consensus suggested classifying metrics as either being non‐instrumental (self‐report, clinical examination) or instrumental (electromyography [EMG]) (Lobbezoo, Ahlberg, Raphael, et al., 2018). However, there is still uncertainty in respect of the optimisation, improvement, and clinical relevance of SB research metrics and scoring criteria; on how to perform data collection and scoring; and which tools/devices are the best to use.…”
Section: Introductionmentioning
confidence: 99%
“…As suggestions for future studies, a comparison with PSG, considered one of the main SB evaluation instruments so far, is highly recommended. Many authors focus on the concept of scoring the whole spectrum of the masticatory muscle activity (MMA) rather than the scoring of SB events, in order to better define the different manifestations of SB activity [ 24 , 25 ]. For instance, in patients affected by obstructive sleep apnoea (OSA), SB could have a protective role by ending the apnoea event [ 2 ].…”
Section: Discussionmentioning
confidence: 99%